Involvement of IL-6 and GSK3β in impaired sensorimotor gating induced by high-fat diet. (October 2019) - Wakabayashi, Chisato; Kunugi, Hiroshi
Highlights: We evaluated the involvement of IL-6 on prepulse inhibition (PPI) deficits in mice. Plasma IL-6 levels were increased in high-fat diet (HFD)-fed mice. Pretreatment of anti-IL-6 receptor antibody MR16-1 ameliorated PPI deficits. The striatum of HFD-fed mice showed an increase in phosphorylation of GSK3β. MR16-1 might have a beneficial effect on HFD-induced sensorimotor deficits. Abstract: Increased levels of proinflammatory cytokines have been implicated in schizophrenia; however, their pathophysiological roles in abnormal brain dysfunctions remain unclear. We evaluated the effect of proinflammatory cytokines on a high-fat diet (HFD)-induced prepulse inhibition (PPI) deficits in the acoustic startle response. Eight-week-old male C57BL/6J mice were fed a HFD for 3 weeks and then PPI was examined. HFD significantly induced PPI deficits and increased plasma IL-6, but not TNFα, levels. Interestingly, MR16-1 administration during the HFD period ameliorated PPI deficits. Further, in the striatum of HFD-fed mice, phosphorylation of GSK3β, but not GSK3α, was significantly increased; this increase was attenuated by MR16-1, although the protein levels of GSK3α and β were not altered. There were no significant differences in either phosphorylation or protein levels of GSK3α, β in the PFC during the HFD period. These results suggest that increased IL-6 levels during HFD may induce sensorimotor gating deficits, likely through the alteration of striatal GSK3β phosphorylation. MR16-1 might have a beneficial effect on such HFD-induced sensorimotor gating deficits.